Analisis Pola Pengasuhan Anak Usia Dini oleh Orang Tua yang Bekerja pada Shift Malam - farida nur azizah (Bahasa Indonesia, 2026)
ABSTRACT Parenting practices play a crucial role in supporting the growth and development of early childhood. However, families in which parents work night shifts often face unique challenges in balancing occupational responsibilities with childcare duties. This study aims to analyze parenting patterns implemented by parents who work night shifts and to explore the strategies they employ in fostering the development of their young children at the Similar Early Childhood Education Unit (SPS) Prapat Hulu, Babussalam, Southeast Aceh. The research adopted a qualitative approach involving four families whose children were enrolled in SPS Prapat Hulu and whose parents were actively engaged in night-shift work. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that parents employ several adaptive strategies to maintain effective childcare, including structured yet flexible scheduling, the utilization of communication technology, the establishment of meaningful family routines, attention to parents’ physical and psychological well-being, and the practice of open communication with children. The study also highlights the significant role of educational institutions, policy support, and community involvement in assisting families to address the challenges associated with night-shift employment. The findings suggest that, despite the complexities of balancing work and parenting responsibilities, appropriate caregiving strategies combined with adequate social support can contribute positively to children’s development and family well-being. Furthermore, the study emphasizes the need for future longitudinal research to examine the long-term effects of parenting patterns among night-shift worker families on child development and family dynamics. Keywords: Parenting Patterns, Early Childhood, Night-Shift Workers, Family Support, Child Development.